CD82 Restrains Angiogenesis by Altering Lipid Raft Clustering and CD44 Trafficking in Endothelial Cells - Wei, Quan (Circulation, 2014)
BACKGROUND: Angiogenesis is crucial for many pathological processes and becomes a therapeutic strategy against diseases ranging from inflammation to cancer. The regulatory mechanism of angiogenesis remains unclear. Although tetraspanin CD82 is widely expressed in various endothelial cells (ECs), its vascular function is unknown. METHODS AND RESULTS: Angiogenesis was examined in Cd82-null mice with in vivo and ex vivo morphogenesis assays. Cellular functions, molecular interactions, and signaling were analyzed in Cd82-null ECs. Angiogenic responses to various stimuli became markedly increased upon Cd82 ablation. Major changes of Cd82-null ECs were enhanced migration and invasion, likely resulting from the upregulated expression of cell adhesion molecules (CAMs) such as CD44 and integrins at the cell surface and subsequently elevated outside-in signaling. Gangliosides, lipid raft clustering, and CD44-membrane microdomain interactions were increased in the plasma membrane of Cd82-null ECs, leading to less clathrin-independent endocytosis and then more surface presence of CD44. CONCLUSIONS: Our study reveals that CD82 restrains pathological angiogenesis by inhibiting EC movement, lipid raft clustering and CAM trafficking modulate angiogenic potential, and the perturbation of CD82-ganglioside-CD44 signaling attenuates angiogenesis.